Recommendations for the process of classification of dams in Brazil - Sérgio Ricardo Toledo Salgado; Elsa Maria da Silva Carvalho (U.Porto Journal of Engineering, 2023)
The Brazilian National Policy on Dam Safety (PNSB) was enacted in 2010 and there are still many actions to be carried out, especially the classification of dams as to associated hazard potential (PHA) and risk category (RC). The analysis conducted based on the Dam Safety Report 2020 informs that there are 21953 dams distributed throughout the Brazilian territory registered in National Dam Information System (SNISB). However, 14849 (67.64%) of the dams were not classified as RC and 13475 (61.38%) of the dams were not classified as PHA. There are 3724 dams classified as high PHA, 2407 (64.64%) of which are considered small in terms of reservoir capacity. Considering this scenario, bibliographic research was conducted on dam classification criteria used in Brazil, Portugal, International Commission on Large (ICOLD) and United States. In addition, bibliographic research was conducted on two studies that used artificial intelligence-based tools to forecast PHA classification. As a result, this study recommends future research with indicated classification criteria and with applications based on artificial intelligence to forecast PHA classification in Brazil.